Technical application method for enhancing oxidation performance of Fenton reaction by defect-rich carbon-based cocatalyst

By preparing defect-rich carbon-based co-catalysts to strengthen the Fenton reaction, the problems of Fe3+ hydrolysis and Fe2+ regeneration difficulties were solved, efficient oxidation performance and long-term pollutant removal were achieved, and costs and frequent regeneration requirements were reduced.

CN120790193AInactive Publication Date: 2025-10-17NINGXIA BEIGUO ENVIRONMENTAL PROTECTION & ENERGY SAVING CO LTD

Patent Information

Application Number
CN202511191557.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-10-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing Fenton reaction, Fe3+ hydrolysis and Fe2+ regeneration are difficult, resulting in iron sludge formation and low reaction efficiency. In addition, the activated carbon adsorption process is easily saturated and requires frequent regeneration, making it difficult to remove new pollutants in the long term.

Method used

Using defect-rich carbon-based co-catalysts, ZIF-8 was prepared and carbonized under an inert atmosphere to form defect-rich carbon materials, which were used in the Fenton reaction to enhance the Fe3+/Fe2+ cycle efficiency and inhibit Fe3+ hydrolysis, and were coupled with the Fenton system in the form of a filter column.

Benefits of technology

It effectively inhibits Fe3+ hydrolysis, improves Fe2+ regeneration efficiency, broadens pH applicable range, reduces reagent costs, extends the service life of adsorption materials, and achieves efficient oxidation performance and pollutant removal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120790193A_ABST
    Figure CN120790193A_ABST
Patent Text Reader

Abstract

The invention provides a technical application method for strengthening oxidation performance of Fenton reaction by a defect-rich carbon-based cocatalyst, and relates to the technical field of advanced oxidation catalysts for sewage treatment. Zinc nitrate and 2-methylimidazole are assembled in a methanol solution through a template method, a ZIF-8 material is obtained after centrifugal cleaning, the ZIF-8 is further carbonized through pyrolysis, Zn element is evaporated in the pyrolysis process, a porous and defect-rich carbon-based cocatalyst is obtained, the porous and defect-rich carbon-based cocatalyst is introduced into a Fenton oxidation system, circulation of Fe < 3 + > / Fe < 2 + > in the Fenton reaction can be efficiently promoted, and the catalytic activity of the catalyst is improved. Fe < 2 + > regeneration is enhanced, and the generation capability of active species of a Fenton reaction system is enhanced, so that the removal efficiency of pollutants in water is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the field of wastewater treatment advanced oxidation catalysts, in particular to a technical application method for enhancing the oxidation performance of a Fenton reaction by using a defect-rich carbon-based promoter catalyst. BACKGROUND

[0002] In the process of rapid modernization in China, the degradation of new pollutants in various types of sewage and wastewater has become a key concern in the field of water treatment. The mainstream pollutant treatment process is currently the Fenton / Fenton-like process, which generates various types of free radicals with strong oxidizing properties by activating the O-O bond in the oxidizing agent to degrade pollutants. However, the Fe 2+ generated in the reaction is prone to hydrolysis to produce iron sludge and Fe 3+ , which is difficult to regenerate, seriously hindering the application of the technology. 2+

[0003] Currently, the main method for inhibiting the hydrolysis of Fe 3+ in the Fenton reaction process and strengthening the regeneration of Fe 2+ is to add a reducing complexing agent. Through the coordination effect of the complexing agent, Fe 2+ or Fe 3+ in the solution is more stable, and the steric hindrance effect prevents it from directly contacting water, thereby avoiding the further dehydration of Fe 2+ or Fe 3+ to form hydroxide or oxide precipitates; meanwhile, the reducing property or coordination field effect of the complexing agent can accelerate the reduction of Fe 3+ , thereby maintaining the high-efficiency operation of the Fenton system.

[0004] Chinese patent document CN118993298A discloses a method for removing antibiotics in drinking water by using a UV-coupled hydroxylamine to strengthen the Fe 2+ / CaO2 Fenton system. By sequentially adding hydroxylamine hydrochloride, calcium oxide and ferrous sulfate heptahydrate to the drinking water containing the antibiotics, 100% degradation of the antibiotics in the drinking water is achieved under UV light and stirring conditions.

[0005] Chinese patent document CN116212949A discloses a ferric ion complex, a preparation method and application thereof. The ferric ion is stirred with a thiophene carboxylic acid ligand at room temperature and mixed with hydrogen peroxide, thereby generating oxidation active species mainly in the form of hydroxyl radicals, which can effectively degrade triazine, phenol, benzoic acid and antibiotic organic pollutants.

[0006] ​Although the two applications can solve the two defects of the Fenton process, the cost of hydroxylamine hydrochloride or thienyl carboxylic acid ligand itself still greatly limits the practical application of the Fenton process; at the same time, the homogeneous catalyst is difficult to recover after being put into the Fenton system, and the evolution path of the catalyst itself is unknown, which may produce more toxic and polluting by-products.

[0007] At the same time, the activated carbon adsorption process is also an effective separation method for new pollutants. Through excellent adsorption performance, various activated carbons can realize efficient adsorption and removal of coexisting new pollutants. However, due to the limitation of adsorption capacity, the activated carbon adsorption process is prone to saturation problem, and frequent backwashing and regeneration are required during use, which makes it difficult to realize long-term removal of coexisting new pollutants in actual engineering application. SUMMARY

[0008] In view of the shortcomings of the prior art, the application provides a technical application method for enhancing the oxidation performance of a Fenton reaction by using a defect-rich carbon-based catalyst. 3+ / Fe 2+ cycle efficiency, inhibits Fe 3+ hydrolysis, and simultaneously alleviates the accumulation of organic pollutants on the surface of the catalyst, which leads to breakthrough and frequent regeneration of the long-term organic pollutant removal technology. Moreover, the catalyst is convenient to use and can be coupled with the Fenton and Fenton-like oxidation systems through filter columns and filter beds, thereby simultaneously solving the main defects of the Fenton oxidation technology and the activated carbon filtration technology, and the technical goal is easy to achieve.

[0009] To achieve the above object, the application is implemented by the following technical scheme: a technical application method for enhancing the oxidation performance of a Fenton reaction by using a defect-rich carbon-based catalyst, characterized in that: a carbon material rich in defect structures is used as a catalyst, which is put into a Fenton oxidation system to enhance the oxidation and degradation performance of the Fenton reaction system on coexisting organic pollutants.

[0010] Preferably, the preparation steps include the following steps:

[0011] S1. Dissolve zinc nitrate hexahydrate in methanol at a concentration of ≤50g / L to obtain a zinc nitrate alcohol solution, dissolve 2-methylimidazole in methanol at a concentration of ≤50g / L to obtain an imidazole alcohol solution, and add the imidazole alcohol solution to the zinc nitrate alcohol solution at a volume ratio of 1:1, stir until the white precipitate no longer increases, centrifuge and wash with methanol for 2-3 times, and vacuum dry to obtain ZIF-8;

[0012] Place the ZIF-8 in a tube furnace, carbonize at 10℃ / min to 1000℃ under an inert atmosphere for 2 hours, and dry after acid washing to obtain a defect-rich carbon-based catalyst;

[0013] or directly using the defective activated carbon, biochar-like material as a carbon-based co-catalyst;

[0014] S2. The carbon-based co-catalyst obtained in step S1 is put into a Fenton reaction constructed by Fe 2+ and H2O2 under acidic conditions at pH 5 to improve the Fe 2+ regeneration efficiency and pollutant degradation efficiency.

[0015] Preferably, in S1, no more than 5g of zinc nitrate hexahydrate per 100mL of methanol.

[0016] Preferably, in S1, no more than 5g of 2-methylimidazole per 100mL of methanol.

[0017] Preferably, in S1, the volume ratio of imidazole alcohol solution to zinc nitrate alcohol solution is 1:1.

[0018] Preferably, in S2, the tube furnace heating rate is 10℃ / min, the pyrolysis time is 2h, and the pyrolysis carbonization temperature is 800-1000℃.

[0019] The present application provides a technical application method for enhancing the oxidation performance of Fenton reaction by using a defective carbon-based co-catalyst.

[0020] 1. The present application provides a technical application method for enhancing the oxidation performance of Fenton reaction by using a defective carbon-based co-catalyst, compared with the prior art, the defective carbon-based co-catalyst prepared in the present application is rich in a large number of structural defects, and has a strong adsorption property for Fe 3+ and Fe 2+ , which can effectively inhibit the hydrolysis of Fe 3+ and Fe 2+ to produce iron sludge, effectively avoiding the problems of secondary pollution, narrow pH range and high reagent dosage in traditional Fenton process.

[0021] 2. The present application provides a technical application method for enhancing the oxidation performance of Fenton reaction by using a defective carbon-based co-catalyst, compared with the prior art, the Fe 3+ adsorbed by the carbon co-catalyst in the present application can be rapidly reduced to Fe 2+ by dynamic coordination field effect, and the Fe 3+ / Fe 2+ cycle performance is significantly better than that of traditional Fenton, which ensures the continuous and efficient generation of oxidative active species in the system, effectively improves the oxidation reaction performance and iron salt utilization rate. At the same time, compared with the direct use of the co-catalyst for pollutant adsorption, the coupling with the Fenton reaction greatly reduces the adsorption breakthrough rate, effectively improving the convenience of the use process.

[0022] 3. The application provides a technical application method for enhancing the oxidation performance of Fenton reaction by using a defect-rich carbon-based cocatalyst, wherein, compared with the prior art, the cocatalyst used in the application is based on a carbon-based material, and compared with a reducing agent and a complexing agent, the cocatalyst has a wide source and is simple to prepare, and can effectively reduce the use cost of the cocatalyst.

[0023] 4. The application provides a technical application method for enhancing the oxidation performance of Fenton reaction by using a defect-rich carbon-based cocatalyst, wherein, compared with the prior art, the cocatalyst used in the application is in a solid powder type, is easy to be coupled with the Fenton reaction, and has a simple and reliable technical form, and can effectively avoid the problem of increasing the toxicity of the reaction system due to the evolution of the cocatalyst accompanying the reaction. BRIEF DESCRIPTION OF DRAWINGS

[0024] Figure 1 The scanning electron microscope (FESEM) of the prepared cocatalyst in Example 1 and Comparative Examples 1-2;

[0025] Figure 2 The X-ray photoelectron spectrogram (XPS) of the prepared cocatalyst in Example 1 and Comparative Examples 1-2;

[0026] Figure 3 The degradation test of BPA of the prepared cocatalyst in Example 1, ZIF-8 and Comparative Examples 1-2;

[0027] Figure 4 The degradation test of BPA of the prepared cocatalyst in Example 1 under different pH conditions;

[0028] Figure 5 The degradation test of BPA of the prepared cocatalyst in Example 1 in the presence of different anions;

[0029] Figure 6 The degradation test of different pollutants of the prepared cocatalyst in Example 1;

[0030] Figure 7 The degradation test of different pollutants of the prepared cocatalyst in Example 1 in different systems Fe 2+ Regeneration capacity test;

[0031] Figure 8 The column adsorption and oxidation performance test of the prepared cocatalyst in Example 1. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the application will be described clearly and completely below with reference to the drawings in the embodiments of the application. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments of the application. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the protection scope of the application.

[0033] Example 1

[0034] (1) Accurately weigh 4.13 g of zinc nitrate hexahydrate and 4.40 g of 2-methylimidazole, and dissolve the weighed reagents in 100 mL of methanol respectively and stir until completely dissolved;

[0035] (2) Rapidly add the dispersed imidazole alcohol solution to the zinc nitrate alcohol solution, and continue to stir for 12 h to make it uniformly mixed.

[0036] (3) Stop stirring and let it stand and grow for 4 h, and then take it out after the white precipitate no longer grows.

[0037] (4) Place the white precipitate in a centrifuge and centrifuge at a speed of 7000 rad / min for 5 min. ZIF-8 precursor is obtained.

[0038] (5) The ZIF-8 precursor is quickly washed with methanol for 2 times, and placed in a vacuum oven, with a vacuum degree of -75 kPa, a drying temperature of 70°C, and a drying time of 6 h. After complete drying, the obtained solid is thoroughly ground to obtain ZIF-8.

[0039] (6) Place the ZIF-8 in a tube furnace, set the heating rate to 10°C / min, the pyrolysis temperature to 900°C, and the pyrolysis time to 3 h, and perform the carbonization reaction under N2 atmosphere to obtain a black powder.

[0040] (7) The black powder is thoroughly ground and placed in a 2.0 M sulfuric acid solution for acid washing, with an acid washing temperature of 80°C and an acid washing time of 4 h, followed by continuous water washing until neutral, and drying to obtain a nitrogen impurity defect cocatalyst, named cocatalyst-900.

[0041] Comparative Example 1

[0042] (1) Accurately weigh 4.13 g of zinc nitrate hexahydrate and 4.40 g of 2-methylimidazole, and dissolve the weighed reagents in 100 mL of methanol respectively and stir until completely dissolved;

[0043] (2) Rapidly add the dispersed imidazole alcohol solution to the zinc nitrate alcohol solution, and continue to stir for 12 h to make it uniformly mixed.

[0044] (3) Stop stirring and let it stand and grow for 4 h, and then take it out after the white precipitate no longer grows.

[0045] (4) Place the white precipitate in a centrifuge and centrifuge at a speed of 7000 rad / min for 5 min. ZIF-8 precursor is obtained.

[0046] (5) The ZIF-8 precursor was quickly washed twice with methanol, placed in a vacuum oven, set the vacuum degree to-75 kPa, the drying temperature to 70°C, and the drying time to 6 h. After complete drying, the obtained solid was fully ground to obtain ZIF-8.

[0047] (6) The ZIF-8 was placed in a tube furnace, set the heating rate to 10°C / min, the pyrolysis temperature to 800°C, and the pyrolysis time to 3 h, and the carbonization reaction was carried out under N2 atmosphere to obtain black powder.

[0048] (7) The black powder was fully ground and placed in a 2.0M sulfuric acid solution for acid washing, the acid washing temperature was 80°C, the acid washing time was 4 h, and then continuous water washing was carried out until neutral, and drying was carried out to obtain a nitrogen impurity defect promoter, named as promoter-800.

[0049] Comparative Example 2

[0050] (1) 4.13 g of zinc nitrate hexahydrate and 4.40 g of 2-methylimidazole were accurately weighed and dissolved in 100 mL of methanol respectively, and stirred until completely dissolved.

[0051] (2) The dispersed imidazole alcohol solution was quickly added to the zinc nitrate alcohol solution, and continuously stirred for 12 h to make it uniformly mixed.

[0052] (3) The stirring was stopped and the growth was allowed to stand for 4 h, and then the white precipitate was taken out after the white precipitate no longer grew.

[0053] (4) The white precipitate was placed in a centrifuge and centrifuged at a speed of 7000 rad / min for 5 min to obtain ZIF-8 precursor.

[0054] (5) The ZIF-8 precursor was quickly washed twice with methanol, placed in a vacuum oven, set the vacuum degree to-75 kPa, the drying temperature to 70°C, and the drying time to 6 h. After complete drying, the obtained solid was fully ground to obtain ZIF-8.

[0055] (6) The ZIF-8 was placed in a tube furnace, set the heating rate to 10°C / min, the pyrolysis temperature to 1000°C, and the pyrolysis time to 3 h, and the carbonization reaction was carried out under N2 atmosphere to obtain black powder.

[0056] (7) The black powder was fully ground and placed in a 2.0M sulfuric acid solution for acid washing, the acid washing temperature was 80°C, the acid washing time was 4 h, and then continuous water washing was carried out until neutral, and drying was carried out to obtain a nitrogen impurity defect promoter, named as promoter-1000.

[0057] Experimental Example 1

[0058] The catalysts prepared in Example 1 and Comparative Examples 1-2 were subjected to SEM test, and the results are as followsFigure 1 As shown

[0059] Figure 1 The scanning electron microscope images of ZIF-8 and three kinds of catalyst supports prepared in Example 1 and Comparative Examples 1-2 show that ZIF-8 presents a regular dodecahedron crystal structure with clear edges. When the pyrolysis temperature is increased from 800℃ to 900℃, the standard crystal structure of ZIF-8 changes due to the melting of Zn and carbonization of the carbon base in the raw material, but the basic morphological characteristics can be maintained. When the pyrolysis temperature is further increased to 1000℃, the crystal structure collapses obviously with the continuous blowing of nitrogen and the gasification and evaporation of Zn element, and the prepared carbon-based catalyst support with defects tends to be amorphous carbon.

[0060] Experimental Example 2

[0061] The catalysts prepared in Example 1 and Comparative Examples 1-2 were subjected to XPS test, and the results are shown in Figure 2 As shown

[0062] Figure 2 The X-ray photoelectron spectrograms of the three kinds of catalyst supports prepared in Example 1 and Comparative Examples 1-2 show that the three kinds of catalyst supports prepared all only contain C1 s, N1 s and O1S peaks, indicating that the pyrolysis temperature in the range of 800-1000℃ can effectively evaporate the Zn element in the ZIF-8 precursor. At the same time, it can be seen from the N1 s fine spectrum of the three kinds of catalyst supports that Comparative Example 1 only contains pyridine nitrogen and pyrrole nitrogen, while Example 1 and Comparative Example 2 both contain pyridine nitrogen, pyrrole nitrogen and graphite nitrogen. The nitrogen element in the three kinds of catalyst supports is mainly pyridine nitrogen, and the pyridine nitrogen content of the three kinds of catalyst supports from high to low is catalyst support-900, catalyst support-1000 and catalyst support-800 in turn, indicating that the carbon-based catalyst support with rich pyridine nitrogen type defects is successfully prepared.

[0063] Application Example 1

[0064] (1) Accurately weigh 136.8 mg of BPA and dissolve it in 500 mL of ultrapure water, add NaOH particles and ultrasonic dispersion until completely dissolved, adjust the pH to 7.0±0.2 with HNO3, and then dilute to 1000 mL to obtain a 600 μM BPA stock solution.

[0065] (2) Accurately weigh 404 mg of iron nitrate nonahydrate and dissolve it in 50 mL of dilute nitric acid (pH<2), adjust the pH to 2, and then dilute to 100 mL to obtain a 10 mM Fe 3+ stock solution.

[0066] (3) The degradation experiment was carried out in a 120 mL beaker, 10 mL of BPA stock solution and 90 mL of ultrapure water were added to the beaker, the pH was adjusted to 4.0, and then the sample was taken quickly, and then 0.4 mL of Fe 3+Stock solution, 10 mg of co-catalyst (Co-catalyst-800, or Co-catalyst-900, or Co-catalyst-1000, or without catalyst) with 50 μL of 30% hydrogen peroxide solution and timing, sampling at a specific time.

[0067] (4) 1 mL of each sample, using a 0.22 μm filter membrane to filter the co-catalyst, and quickly quench with 0.5 mL of methanol. The sample is detected using a Uitmate-3000 type ultra-high performance liquid chromatograph with a Shimadzu C18 reversed-phase chromatographic column, the mobile phase is water: acetonitrile = 60:40, the mobile phase flow rate is 0.2 mL / min, and the detection wavelength is 278 nm.

[0068] The results of the comparative experiments are shown in Figure 3 As shown, when no co-catalyst is added, the degradation rate of Fe 3+ / H2O2 system on BPA is only 68.0% in 7 min, and when co-catalyst-800-1000 exists in the system, the degradation rates of BPA are 92.4%, 100% and 85.8% respectively, indicating that the prepared co-catalyst can effectively strengthen the Fenton-like system to produce more active species. Among them, co-catalyst-900 shows the best co-catalyst effect, due to its having the most pyridine defects.

[0069] Application Example 2

[0070] (1) Compared with Application Example 1, the pH of the beaker degradation experiment is adjusted to 2, 3, 4, 5 respectively.

[0071] (2) Compared with Application Example 1, all co-catalyst experiments are co-catalyst-900.

[0072] (3) Compared with Application Example 1, the reaction time is extended to 20 minutes.

[0073] The results of the comparative experiments are shown in Figure 4 As shown, when the pH is 2, 3, 4, 5 respectively, the degradation rate of Fe 3+ / H2O2 / co-catalyst-900 system on BPA is 60.0%, 100%, 100% and 100% respectively in 20 min, indicating that the prepared co-catalyst can effectively prevent Fe 3+ and the generated Fe 2+ from hydrolysis, thereby widening the pH range of the Fenton-like reaction, reducing the generation of iron sludge and the amount of iron salt.

[0074] Application Example 3

[0075] (1) Compared with Application Example 2, all beaker degradation experiments are carried out at pH = 4.

[0076] (2) Compared with Application Example 2, all the experimental catalysts are catalyst-900.

[0077] (3) Compared with Application Example 2, the reaction time is 7 minutes.

[0078] (4) Compared with Application Example 2, there are 0.15 mM of chloride ions, carbonate ions and nitrate ions in the system.

[0079] The experimental results are shown in Table 2. Figure 5 As shown in Table 2, when the pH is 2, 3, 4 and 5, respectively, the degradation rate of BPA in the Fe 3+ / H2O2 / catalyst-900 system within 7 minutes is 60.0%, 100%, 100% and 100%, respectively, indicating that the prepared catalyst can enhance the performance of Fenton reaction under complex water quality conditions and has great practical application potential.

[0080] Application Example 4

[0081] (1) Compared with Application Example 2, all beaker degradation experiments are carried out at pH = 4.

[0082] (2) Compared with Application Example 2, all the experimental catalysts are catalyst-900.

[0083] (3) Compared with Application Example 2, the reaction time is 7 minutes.

[0084] (4) Compared with Application Example 2, the pollutants in the system are methyl orange (MO), acetaminophen (AAP), sulfamethoxazole (SMX), methylene blue (MB) and atrazine (ATZ), respectively.

[0085] The experimental results are shown in Table 3. Figure 6 As shown in Table 3, the degradation rate of MO, AAP, SMX, MB and ATZ in the Fe 3+ / H2O2 / catalyst-900 system within 7 minutes is 100%, 100%, 82.3%, 100% and 59.8%, respectively, indicating that the prepared catalyst can enhance the Fenton reaction to degrade various complex pollutants and has great practical application potential.

[0086] Application Example 5

[0087] (1) Accurately weigh 1 g of o-phenanthroline and dissolve it in 80 mL of ultrapure water. After adding concentrated hydrochloric acid to completely dissolve, dilute to 100 mL to obtain o-phenanthroline color developing solution.

[0088] (2) Accurately weigh 0.01961 g of ferrous ammonium sulfate and dissolve it in 100 mL of ultrapure water to obtain Fe 2+ standard solution.

[0089] (3) Accurately pipette 0.5, 1.0, 2.0, 3.0, 4.0, 5.0 Fe 2+ Standard solution in 50 mL cuvette, corresponding to concentrations 5, 10, 20, 30, 40 and 50 μΜ, then add 2 mL phenanthroline color developing solution and dilute to 50 mL. Shake well and measure the absorbance of each solution at 510 nm after 15 min color development. The fitting results of the standard curve are ([absorbance] = 0.01134 * [Fe 2+ concentration] + 0.0009, R 2 = 0.9999).

[0090] (4) Add 100 mL ultrapure water to a 120 mL beaker, add 0.4 mL Fe 3+ stock solution, then adjust the solution to pH = 4 and take samples. Add a: 10 mg of co-catalyst-900; b: 0.05 mL of 30% hydrogen peroxide; c: 0.05 mL of 30% hydrogen peroxide + 10 mg of co-catalyst-900 to the beaker, respectively, and take samples at 10, 20, 30 min for color development detection, and calculate the Fe 2+ yield of the system according to the standard curve.

[0091] The experimental results are shown in Figure 7 Table 1, it can be found that when only hydrogen peroxide is present, the Fe 2+ yield at 10, 20 and 30 min is 17.82%, 24.75% and 30.71% respectively, which is due to the reducing property of hydrogen peroxide itself. At the same time, only the co-catalyst-900 system has Fe 2+ conversion rates of 20.72%, 28.78% and 32.60% at 10, 20 and 30 min, which are slightly higher than that of the hydrogen peroxide system alone, indicating that the nitrogen impurity defect carbon-based co-catalyst prepared can effectively adsorb free Fe 3+ to the defect site, and rapidly reduce Fe 3+ to Fe 2+ by the dynamic coordination field effect of the single atom-like and then release it again. The hydrogen peroxide + co-catalyst-900 system shows the highest Fe 2+ conversion rate, reaching 58.84% at 30 min, indicating that the prepared co-catalyst can effectively accelerate the Fe 3+ / Fe 2+ cycle to enhance the performance of the Fenton-like reaction.

[0092] Application Example 6

[0093] (1) Accurately weigh 0.1141 g of BPA and dissolve it in 500 mL of ultrapure water, add NaOH particles and ultrasonic dispersion until completely dissolved, dilute to 1000 mL, then adjust the pH to 3.0 using HNO3 to obtain a 500 μΜ BPA stock solution.

[0094] (2) Accurately weigh 1.616 mg of ferric nitrate nonahydrate into 50 mL of dilute nitric acid (pH < 2), adjust the pH to 3, then add 0.567 mL of 30% hydrogen peroxide, and dilute to 100 mL to obtain a Fenton-like stock solution.

[0095] (3) Accurately weigh 1 g of coconut shell activated carbon promoter into a glass column with an inner diameter of 6 mm, add the BPA stock solution to allow natural filtration under gravity and time, and sample according to different times, with a sampling volume of 1 mL each time.

[0096] (4) After the filler column penetrates for 2.3 h, add 100 mL of Fenton-like stock solution, stand for 0.5 h, then filter, and add 300 mL of ultrapure water in three portions to obtain an activated and regenerated column.

[0097] (5) Add 16.16 mg of ferric nitrate nonahydrate and 5.667 mL of 30% hydrogen peroxide to the BPA stock solution described in (1), add it to the activated and regenerated column, and allow natural filtration under gravity and time, and sample according to different times, with a sampling volume of 1 mL each time.

[0098] (6) The samples are detected using a Ultimate-3000 ultra-high performance liquid chromatograph with a Shim-pack C18 reversed-phase chromatographic column, with a mobile phase of water:acetonitrile = 60:40, a mobile phase flow rate of 0.2 mL / min, and a detection wavelength of 278 nm.

[0099] The experimental results are shown in Figure 8 The filtration column penetrates for 2.3 h, and the activated and regenerated column does not penetrate BPA within this time period. Furthermore, no BPA penetration is found when the reaction time is further extended to 3.0 h. The results show that coconut shell activated carbon has good adsorption effect on pollutants, and as a promoter, it can generate active species by in-situ regeneration of Fe 2+

[0100] Although embodiments of the present application have been shown and described, it is to be understood that various modifications, substitutions, replacements and changes can be made to these embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.​

Claims

1. A technical application method for enhancing the oxidation performance of the Fenton reaction by using a defect-rich carbon-based promoter, characterized in that: A carbon material rich in defect structures is used as a co-catalyst and put into a Fenton oxidation system to enhance the oxidative degradation performance of the Fenton reaction system on coexisting organic pollutants.

2. The technical application method of a defect-rich carbon-based co-catalyst to enhance the oxidation performance of the Fenton reaction according to claim 1, characterized in that: Specifically comprising the following preparation steps: S1. Dissolve zinc nitrate hexahydrate in methanol at a concentration of ≤50 g / L to obtain a zinc nitrate alcohol solution, dissolve 2-methylimidazole in methanol at a concentration of ≤50 g / L to obtain an imidazole alcohol solution, add the imidazole alcohol solution to the zinc nitrate alcohol solution at a volume ratio of 1:1, stir until the white precipitate no longer increases, centrifuge, wash with methanol 2-3 times, and vacuum dry to obtain ZIF-8; The ZIF-8 was placed in a tube furnace and heated to 1000°C at a rate of 10°C / min under an inert atmosphere for 2 hours, followed by acid washing and drying to obtain a defect-rich carbon-based co-catalyst. S2. Add the carbon-based co-catalyst obtained in step S1 into the Fe 2+ The Fenton reaction was constructed with H2O2 under acidic conditions of pH 5 to increase the Fe 2+ Regeneration efficiency and pollutant degradation efficiency.

3. The technical application method of a defect-rich carbon-based co-catalyst to enhance the oxidation performance of the Fenton reaction according to claim 2, characterized in that: In S1, the amount of zinc nitrate hexahydrate in 100 mL of methanol does not exceed 5 g.

4. The technical application method of a defect-rich carbon-based co-catalyst to enhance the oxidation performance of the Fenton reaction according to claim 2, characterized in that: In S1, the amount of 2-methylimidazole in every 100 mL of methanol does not exceed 5 g.

5. The technical application method of a defect-rich carbon-based co-catalyst to enhance the oxidation performance of the Fenton reaction according to claim 2, characterized in that: In the S1, the volume ratio of the imidazole alcohol solution to the zinc nitrate alcohol solution is 1:

1.

6. The technical application method of a defect-rich carbon-based co-catalyst to enhance the oxidation performance of the Fenton reaction according to claim 2, characterized in that: In S2, the heating rate of the tubular furnace is 10°C / min, the pyrolysis time is 2 hours, and the pyrolysis carbonization temperature is 800-1000°C.

Citation Information

Patent Citations

  • Ferric iron complex as well as preparation method and application thereof

    CN116212949A

  • Method for removing antibiotics in drinking water by using UV coupled hydroxylamine enhanced Fe2+ / CaO2 Fenton system

    CN118993298A

Cited By

  • Pickling defect engineering modified iron monatomic catalyst as well as preparation method and application thereof

    CN121972206A

  • Pickling defect engineered iron monatomic catalyst, method for preparing same, and use thereof

    CN121972206B

  • Interlayer confinement heteroatom doped carbon material and preparation method and application thereof

    CN122126825A